Issues of Page Representation and Organisation in Web Browser's Revisitation Tools - Cockburn, Andy; Greenberg, Saul (Australasian Journal of Information Systems, 2000)
Many commercial and research WWW browsers include a variety of graphical revisitation tools that let users return to previously seen pages. Examples include history lists, bookmarks and site maps. In this paper, we examine two fundamental design and usability issues that all graphical tools for revisitation must address. First, how can individual pages be represented to best support page identification? We discuss the problems and prospects of various page representations: the pages themselves, image thumbnails, text labels, and abstract page properties. Second, what display organisation schemes can be used to enhance the visualisation of large sets of previously visited pages? We compare temporal organisations, hub-and spoke dynamic trees, spatial layouts and site maps.